Perilaku Perawat dalam Manajemen Nyeri Non Farmakologi pada Neonatus Pendekatan Theory of Planned Behavior (TPB) - Tiur Trihastutik; Ida Berliana; Ilya Krisnana; Iqlima Dwi Kurnia; Hidayat Arifin (Universitas Airlangga, 2019)
Introduction: Pain in the neonate may result in negative behavior, physiology and metabolic responses. This study aims to analyze the behavior of nurses in the implementation of non-pharmacological pain management in neonates who performed minor invasive action with the approach of Theory of Planned Behavior (TPB).Methods: This research was a descriptive study of analysis with research design cross sectional. The population of this study were nurses working in the neonatal ward and neonatal intensive care unit dr. Soetomo general Hospital Surabaya. Total sample of 55 respondents selected using simple random sampling. The independent variable was the background factor of age, education, knowledge, attitude, subjective norm, perceived behavior control (PBC) and intention. Dependent variable was nurse’s attitude. The data were obtained using questionnaires then analyzed using logistic regression with a degree of significance of 0.05.Results: Background factor age (p = 0.02) and knowledge (p = 0.004) correlated with attitude, education (p = 0.023) correlated with subjective norm, knowledge (p = 0.004) related to PBC, attitude (p = 0.010) and subjective norm (p = 0.006) relate to intention, and intention is related to behavior (p = 0.024).Conclusion: This study concludes that the management of behavior to be more directed to the factors that relate in shaping the behavior of knowledge, attitude, education, subjective norms, and intention.